Pengembangan Alat Permainan Puzzle Alquran untuk Kemampuan Menghafal pada Anak Kelompok B PAUD Sabilal Muhtadin Tembilahan Hulu Indragiri Hilir Riau - Bima Haryani; Nurkamelia Mukhtar AH; Heldanita; Nurhayati Nurhayati; Ahmad Shofi Mubarak (STAI Auliaurrasyidin Tembilahan, 2023)
The convenient process of teaching and learning are things that teachers should consider to get maximum results. This study aims at knowing the feasibility of quranic puzzles to improve early childhood memorization skills. It is a Research and Development (R&D) that adopts the Borg and Gall model. This was conducted on 8 students of group B of PAUD Sabilal Muhtadin Tembilahan Hulu. Data was collected by using questionnaires, interviews, observations, and documentation. The data was then analyzed by using statistics with Likert scale measurements. The findings revealed that the average assessment of a) media experts were at 85.7% (Very Feasible), b) material experts were at 94.2% (Very Feasible), c) class teachers were at 83.9% (Very Feasible); and the results of pre-test tests (41.74%) and posttests (80.35%) of product development increased by 38.61%. Thus, quranic puzzles are feasible for improving the memorization ability of group B students of PAUD Sabilal Muhtadin Tembilahan Hulu Indragiri Hilir Riau.